Regulatory Support, Quality Standards, and Strategic Partnerships in the Development of Micro, Small, and Medium Food Enterprises (Food SMEs) in Indonesia: Dukungan Regulasi, Standar Kualitas, dan Kemitraan Strategis dalam Pengembangan Usaha Mikro, Kecil, dan Menengah Pangan (Food SMEs) di Indonesia - Gary Putra Etwanto; Handy Setyawan; Hendy Endarwan; Muhammad Dini Asmara; Marah Kerma Mardame Manurung; Rendy Riyanto (OGZ Research & Publishing, 2025)
Objective : This study aims to comprehensively analyze the institutional ecosystem that supports the sustainability and competitiveness of Indonesia's Food Micro, Small, and Medium Enterprises (SMEs). Methods : Using a descriptive policy analysis approach, the research identifies and maps three core pillars that determine the development of the sector: (1) regulatory compliance and quality standards, (2) government and cooperative support, and (3) strategic partnerships and initial funding. The data were derived from official policy documents, institutional programs, and community-based engagement with Food SME actors. Research results : The study finds that certifications such as Halal, BPOM, P-IRT, NKV, and HACCP are essential to ensure food safety, consumer confidence, and market access. Government bodies and cooperatives enhance SME capacity through training, financial support, and resource sharing, while partnerships with State-Owned Enterprises (PKBL) and private firms (CSR) contribute capital, management guidance, and innovation support.